Intensitas Pembelian Makanan Online Tidak Berpengaruh Signifikan terhadap Kualitas Diet dan Status Gizi Mahasiswi IPB: The Intensity of Online Food Purchasing Not Significantly Affected the Diet Quality and Nutritional Status of IPB’s Female Students - Sardi, Lorita Amanda; Aries, Muhammad (Jurnal Ilmu Gizi dan Dietetik, 2023)
The increase of intensity using online food delivery applications has not only give positive impact but also negative impact on lifestyle and health. An application system that provides maximum access can have an impact on uncontrolled types and amounts of food purchased. This study aimed to analyze the relationship between the intensity of online food purchasing with diet quality and nutritional status of IPB female students. This research was conducted in February-March 2023 using a cross-sectional research design, involving 95 active female students of IPB who were selected by purposive sampling. Data collection was carried out through interviews and self-administered online. Anthropometric data obtained through direct measurements. Data analysis used Microsoft Excel 2010 and IBM SPSS Statistics 21. There was no significant relationship between the intensity online food purchasing on diet quality and nutritional status (p>0.05). Female students are advised to pay attention to their diet by consuming food according to the principles of balanced nutrition and paying attention to variety, adequacy, and reducing consumption of high energy density foods to maintain diet quality and good nutritional status.